1999
DOI: 10.1002/hep.510300222
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin alone or combined with emergency sclerotherapy in the treatment of acute esophageal variceal bleeding: A prospective randomized trial

Abstract: Recent trials have shown that somatostatin (SMT) is as effective as sclerotherapy in the treatment of acute variceal bleeding and that the combination of both treatments is more effective than sclerotherapy alone. To assess whether the addition of sclerotherapy improves the efficacy of SMT alone, all patients admitted to our unit with gastrointestinal bleeding and with suspected cirrhosis received a continuous infusion of SMT (250 g/h). Endoscopy was performed between 1 and 5 hours later, and patients with eso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
10

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 29 publications
4
75
0
10
Order By: Relevance
“…34 It has also been demonstrated that the addition of sclerotherapy significantly improves the efficacy of SST alone for the treatment of acute variceal bleeding. 35 The results of our study support the beneficial role of SST in combination with endoscopic therapy but not OCT in the optimal management of BEVs. The 6-week rebleeding and mortality in our study was low, in accordance with recent studies who found a vast improvement in the outcome of acute bleeding episode in cirrhotics.…”
Section: Discussionsupporting
confidence: 70%
“…34 It has also been demonstrated that the addition of sclerotherapy significantly improves the efficacy of SST alone for the treatment of acute variceal bleeding. 35 The results of our study support the beneficial role of SST in combination with endoscopic therapy but not OCT in the optimal management of BEVs. The 6-week rebleeding and mortality in our study was low, in accordance with recent studies who found a vast improvement in the outcome of acute bleeding episode in cirrhotics.…”
Section: Discussionsupporting
confidence: 70%
“…Existem estudos que recomendam sua utilização precocemente, antes mesmo da endoscopia. No entanto, a associação com a escleroterapia deveria ser limitada àqueles casos em que existe instabilidade hemodinâmica (choque) ou sangramento ativo no momento do exame (41) . Espera-se que outros estudos referendem o posicionamento aqui assumido, para que se possa, então, propor uma conduta mais definitiva.…”
Section: Discussionunclassified
“…No entanto, recentemente (41) , foi demonstrado que o uso combinado só apresenta vantagens à utilização isolada de somatostatina em pacientes com alto risco de insucesso com o uso da terapia farmacológica, ou seja, em pacientes em choque ou naqueles com sangramento ativo durante a endoscopia.…”
unclassified
“…4,5 Even in nonactive bleeders, sclerotherapy offers a therapeutic advantage. 6 Thus, endoscopic therapy is recommended in nonactive bleeders, although specific, randomized, clinical trials are lacking. 4 AGUSTÍN ALBILLOS, M.D.…”
Section: Banares R Albillosmentioning
confidence: 99%
“…Interferon was used to treat non-A non-B hepatitis starting in the 1980s, at least in clinical trials. 6 When anti-HCV testing became available in the early 1990s, a growing number of patients started antiviral treatments.…”
Section: Peripheral Blood Count Abnormalities Among Patients With Hepmentioning
confidence: 99%